Penerapan Barcode Scanner Pada Sistem Penjualan E-Koperasi Sekolah Berbasis Android - M. Rizky Fadhilah; A. Ferico Octaviansyah Pasaribu; Yusra Fernando (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
This research aims to address issues related to the management of school cooperatives, particularly concerning the recording of cash and credit transactions. To tackle these challenges, the author has developed an E-Cooperative sales information system based on both website and mobile platforms, with a focus on utilizing barcode scanners for transaction recording. The system's development employed the Extreme Programming (XP) methodology, known for its speed, efficiency, and flexibility. Evaluation of the system was conducted using black box testing to assess its functionality and ISO 25010 testing to measure how well it meets user requirements in terms of efficiency, effectiveness, and suitability. The implementation of this E-Cooperative sales information system is expected to enhance efficiency and accuracy in recording school cooperative sales, effectively addressing issues associated with transaction recording. Research findings indicate that the Extreme Programming (XP) approach served as a successful foundation for system design, resulting in the successful development of both website and mobile platforms. Additionally, the ISO 25010 and black box testing yielded positive results, with functionality scoring 100%, sustainability at 91.44%, and black box testing achieving a percentage score of 91.74%.